Prototipe Sistem Deteksi Jarak Kendaraan Roda Empat Untuk Mengurangi Angka Kecelakaan Berbasis Arduino - Arief Rahman Wahid; Khozainuz Zuhri; Fatimah Fahurian (Universitas Mitra Indonesia, 2022)
Based on the research, we need a technology that can be used to monitor the distance when driving in order to reduce the rate of road accidents. The purpose of the author is to make a device on vehicles using Arduino. So the author makes a solution with a report entitled